The Effect of Service Quality, Marketing Mix and Brand Image on Customer Loyalty in Banking Industry - Leo Nardo Setia Budi Djojo; Andriya Risdwiyanto; Moh Gifari Sono; Kusnanto Darmawan; Muhamad Risal Tawil (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The growth of banking is currently accelerating significantly. The rapid expansion and development of technology, information, machinery, and heavy equipment, particularly communication technology, is to blame for this transition. This study aims to examine how customer loyalty in Islamic banks is impacted by marketing mix, brand image, and service quality. This study uses quantitative methods. The research was carried out between June and August of 2022. Active users of Islamic banks make up the research sample. Primary data were used in this investigation, and they were obtained by employing a questionnaire and a random sample technique. The consumers of Islamic banks are the subject of this study. The findings of this study suggest that customer loyalty in Islamic banks is positively and significantly influenced by the marketing mix, brand image, and service quality, partially and simultaneously.